Defect and interstitial B synergistically promote the stability and H2 dissociation of Pd6 supported by graphene. (1st August 2022) - Ma, Li-Juan; Wang, Jianfeng; Jia, Jianfeng; Wu, Hai-Shun
Abstract: As a potential hydrogenation catalyst, palladium nanoparticles supported by graphene encounter three major problems: transition metal agglomeration, interstitial H atom, and the competition between desorption of H2 and Pdn -Hx complex from graphene sheet. In this paper, defects and interstitial B are used to promote the stability and H2 dissociation of Pd6 supported by graphene. The introduction of defects increases the binding energy of Pd, Pd6 and Pd6 B to graphene by a factor of 5–7 and 7–9 before and after hydrogen adsorption, respectively. It indicates that defects can effectively avoid the desorption competition between Pdn Hx and hydrogen molecules. Moreover, the energy barrier of dissociation for the first hydrogen molecule on Pd6 B/C49 is 0.49 eV, which is lower than 0.75 eV on Pd6 /C49 and 0.69 eV on Ti6 /C49 . Graphical abstract: Image 1 Highlights: Defects increase the binding energies of Pd, Pd6, Pd6 B on graphene by 5–7 times. Defects make sure Pd6 /G remains stable after hydrogen adsorption/desorption. Defects effectively avoid the desorption competition between Pdn Hx and H2 . B hinders the interstitial H and makes the H2 dissociation easier. Pd6 B supported by defective graphene is promising catalysts for hydrogenation.